Effects of quercusinfectoria semi-purified fractions on morphological changes, mineralisation and alkaline phosphatase (alp) activity of human fetal osteoblast cell line (hfob 1.19) - Mazlan, Fairuza Munirah (Universiti Sains Malaysia, 2016)
Osteoporosis is a serious disease of the bones. Quercus infectoria (QI) was reported to possess great medicinal values and possible to have an anabolic effect on bone metabolism due to antioxidant properties. Present study was performed to investigate the effect of semi-purified fractions of QI on the proliferation, alkaline phosphatase (ALP) activity, mineralisation and the morphology of hFOB 1.19. Semi-purified fractions of QI (Fraction A and Fraction B) were prepared by column chromatography methods. The hFOB I. 19 were cultured in Dulbecco' s modified eagle F 12 medium (DMEM Fl2) supplemented with a 10% fetal bovine serum (FBS), a 1 % penicillin/streptomycin and then were treated with Fraction A and Fraction B at various concentration (0. 1 to 99 .0 µg/ml) for 72 hours. EC50 for positive control and fractions groups were measured by using MTI assay. Cell proliferation assay was performed to compare the number of cells viability after being treated from day 1 until day 14. The levels of ALP were measured at day 1, 3, 7, 10, and 14 by using ELISA and were compared among negative control, pamidronate, Fraction A and Fraction B. In addition, morphology of hFOB 1 .19 was observed by using inverted microscope and mineralisation of hFOB 1 .19 was determined by von Kossa staining for phosphate deposition and Alizarin red S staining for calcium deposition. The EC50 of hFOB 1.19 treated with Fraction A and Fraction B was 8.86 µg/ml and 9.92 µg/ml, respectively.